Lithuanian, Russian, Polish istoriography with respect to the Poland - Lithuania union - Mečislovas Jučas (Lietuvos Istorijos Studijos)
The investigations in the Poland-Lithuania union were carried out first in Polish and Russian historiography and later in the Lithuanian one. During the 30-40's the latter studies dealt with the earliest pre-union Lithuanian history and emphasized the independent, long-lasting monarchy and the Lithuanian statehood inside the union. Signing the Krėva treaty in 1385, Jogaila did not think about incorporating Lithuania into Poland but intended to rule both states by himself. Thus, in 1385, only a personal inter-state relationship was stated (A. Šapoka). After the restoration of an independent Lithuanian ruler dynasty in 1392, Jogaila possessed no power in Lithuania and did not issue any documents (K. Jablonskis). The rule of Jogaila and his heirs in Lithuania was interrupted. Such a situation remained unchanged until the Lublin union, which did not abolish the Lithuanian state but constituted the union of two states (A. Šapoka, K. Avižonis, B. Dundulis). However, after the Lublin union, Lithuania was left "with limited statehood" (J. Jakštas). The 17th and 18th centuries were the centuries of rapprochement rather than merging of two states and two political nations (A. Šapoka). During Soviet times, Lithuanian historiography, influenced by Russian historians' works, evaluated the Lublin union negatively, describing it as the burial of the Lithuanian state, the intensification of noble privileges, and an obstacle to social progress (J. Jurginis).